2012
DOI: 10.1007/s00253-012-4357-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus salivarius, Lactobacillus reuteri, and Pediococcus acidilactici on the nematode Caenorhabditis elegans include possible antitumor activity

Abstract: This study examined the effects of three lactic acid bacteria (LAB) strains on the nematode Caenorhabditis elegans. Lactobacillus salivarius, Lactobacillus reuteri, and Pediococcus acidilactici were found to inhibit the development and growth of the worm. Compared to Escherichia coli used as the control, L. reuteri and P. acidilactici reduced the lifespan of wild-type and short-lived daf-16 worms. On the contrary, L. salivarius extended the lifespan of daf-16 worms when used live, but reduced it as UV-killed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Studies in C. elegans have shown a mildly beneficial effect in terms of both life and health span for nematodes grown on some strains of Lactobacillus (Ikeda et al, 2007;Lee et al, 2011), although the results are highly strain-dependent and are also affected by factors such as proliferative capability of the bacteria. Some lactic acid bacteria have also been shown to have a detrimental effect on C. elegans lifespan (Fasseas et al, 2013).…”
Section: Probiotic Effects On Lifespanmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in C. elegans have shown a mildly beneficial effect in terms of both life and health span for nematodes grown on some strains of Lactobacillus (Ikeda et al, 2007;Lee et al, 2011), although the results are highly strain-dependent and are also affected by factors such as proliferative capability of the bacteria. Some lactic acid bacteria have also been shown to have a detrimental effect on C. elegans lifespan (Fasseas et al, 2013).…”
Section: Probiotic Effects On Lifespanmentioning
confidence: 99%
“…2A). Several studies Fasseas et al, 2013;Komura et al, 2013;MacNeil et al, 2013) have ruled out the involvement of DAF-16 in probiotic-mediated lifespan extension, indicating that there are multiple independent pathways affecting C. elegans longevity.…”
Section: Pathogen Protective Effectsmentioning
confidence: 99%
“…These last three are probably involved in protection against bacterial pathogens (Evans et al, 2008;Zavalova et al, 2006). It has been shown that TLPs are up-regulated on bacterial infection in C. elegans (Fasseas et al, 2012). Seven TLPs were found in the full dataset, four of which contained a predicted secretion signal.…”
Section: Most Abundant Transcriptsmentioning
confidence: 99%
“…Three lactic bacteria strains, Lactobacillus salivarius , Lactobacillus reuteri , and Pediococcus acidilactici , have been found to hinder the worm's development and growth, obstruct the germ cells growth, and induce the gene expressions involved in pathogen response [28]. …”
Section: Interactions Between Microbial Pathogens and C Elegansmentioning
confidence: 99%